Modelling ligand-receptor interactions: from multivalent to Linker-mediated - Xia, Xiuyang (Nanyang Technological University, 2023)
Ligand-receptor interactions are not only fundamental principles of various biological processes but also provide a practical mechanism for self-assembly in various artificially engineered systems. In this thesis, we aim to offer an in-depth understanding of matters related to ligand-receptor interactions, particularly with a multivalent and linker-mediated nature. Firstly, we focus on the super-selectivity that emerges from the cooperativity of multivalent binding. We show that maximum selectivity occurs at intermediate binding energy and can be significantly larger than the weak binding limit for highly uniform receptor distributions. These results challenge the common belief in the biophysics community that weaker individual ligand-receptor binding always enhances the selectivity of multivalent nanoparticle binding. Secondly, we introduce the linker-mediated strategy and reveal non-trivial entropy-driven phase behavior in two valence-limited systems: linker-mediated DNA-coated colloids and linker-mediated vitrimers. We suggest a new axis for realizing programmable self-assembly of the DNA-coated colloidal system and provide an entropy-driven mechanism for crosslinking and thermo-gelling in vitrimers.